2020
DOI: 10.1111/bph.15070
|View full text |Cite
|
Sign up to set email alerts
|

Voltage modulates the effect of μ‐receptor activation in a ligand‐dependent manner

Abstract: Background and Purpose: Various GPCRs have been described as being modulated in a voltage-dependent manner. Opioid analgesics act via activation of μ receptors in various neurons. As neurons are exposed to large changes in membrane potential, we were interested in studying the effects of depolarization on μ receptor signalling. Experimental Approach: We investigated potential voltage sensitivity of μ receptors in heterologous expression systems (HEK293T cells) using electrophysiology in combination with Förste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 48 publications
3
17
1
Order By: Relevance
“…3F,G), and is similar to the voltage-dependent reduction in efficacy observed with other GPCRs (Vickery et al, 2016). Moreover, regulation of MOR by voltage was recently reported (Ruland et al, 2020). The rapid onset of [K 1 ] e -induced effects (within 5 min) indicates that, under these testing conditions, the observed effects are independent of transcription and/or translation and point toward direct signaling events triggered by depolarization.…”
Section: Depolarization-induced Reduction Of Opioid Sensitivity Requisupporting
confidence: 83%
See 2 more Smart Citations
“…3F,G), and is similar to the voltage-dependent reduction in efficacy observed with other GPCRs (Vickery et al, 2016). Moreover, regulation of MOR by voltage was recently reported (Ruland et al, 2020). The rapid onset of [K 1 ] e -induced effects (within 5 min) indicates that, under these testing conditions, the observed effects are independent of transcription and/or translation and point toward direct signaling events triggered by depolarization.…”
Section: Depolarization-induced Reduction Of Opioid Sensitivity Requisupporting
confidence: 83%
“…In contrast, depolarization effects on opioid efficacy were C-Raf independent, agonist-specific (morphine vs DAMGO), and were observed in neurons and HEK cells, suggesting a receptor-mediated mechanism. Voltage can modulate the efficacy of MOR coupling to G proteins and b -arrestin in an agonist-specific manner (Ruland et al, 2020). Altered balance of voltage-regulated G-protein/ b -arrestin activation may explain our E max effects at high DAMGO concentrations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…S1A, B-G). Ligand dependence of the voltage sensitivity, mainly based on a change in efficacy in receptor activation, was additionally reported previously for morphine, Met-enkephalin, DAMGO and fentanyl (Ruland et al, 2020). Therefore, the MOR shows a strong ligand-specific voltage sensitivity.…”
Section: Introductionsupporting
confidence: 62%
“…However, based on the above-mentioned differences between the different opioids, it is important to understand details of ligand-receptor interactions. We recently showed that ligand-induced MOR activity was modulated by the membrane potential, and the effect and extent of this voltage sensitivity was ligand specific (Ruland et al, 2020). Since the first report of voltage sensitivity of the muscarinic M2 receptor (Ben-Chaim et al, 2003), several other GPCRs have been observed to be modulated in their activity depending on the membrane potential.…”
Section: Introductionmentioning
confidence: 99%